MAKNA DAN FUNGSI RITUAL ADAT “DABBA ANA” PADA MASYARAKAT JINGITIU, DI DESA WADUWALLA KECAMATAN SABU LIAE, KABUPATEN SABU RAIJUA. KAJIAN : SEMIOTIK - Malay, Narantoputrayadi Makan; Padji, Yeni (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2021)
This thesis is entitled “The meaning and Function of Dabba Ana Traditional Ceremony in Jingitiu Community at Waduwalla Village, Sabu Liae Sub-District, Sabu Raijua District. Tthis research is conducted to describe The Meaning and function of Dabba Ana Traditional Ceremony using Charles Sanders Pierre’s Semiotic Theory which is emphasized on : (1) sign icon which has same meaning with the appointed meaning inherently, (2) sign index which has casual relation to the appointed sign, and (3) a sign of symbol which has meaning relation to the appointed arbiter sign, the method which is used in conducting this research is descriptive qualitative . Describtive qualitative method can be defined as a research method without using numbers but words or sentences. The result of this research showed that The Meaning and Function of Dabba Ana Traditional Ceremony is a form of life change or self surrender from Jingitiu Community to God as the life giver based on their believes.